Low Salt Diet Counseling as an Effort to Increase Knowledge of Hypertension Patients - Sutriningsih, Ani; Perwiraningtyas, Pertiwi; Metrikayanto, Wahyu Dini (STIKes Patria Husada Blitar, 2021)
The prevalence of hypertension has increased throughout the year. Hypertension spreads widely because of the lack of knowledge and a healthy lifestyle. People's lifestyle which is more practical has an impact on the implementation of inappropriate hypertension diets and triggers various diseases. Based on this phenomenon, it is necessary to increase public knowledge about hypertension diets. The purpose of this activity was to provide counseling about a low-salt diet as an effort to increase knowledge of hypertension patients. The method was done by giving counseling about low salt diet through lectures to 30 hypertension patients who were routinely monitored at the Panti Rahayu Clinic. The pre test showed that almost all of the hypertension patients (80%) were in the poor category of knowledge. The post test showed that after being given counseling the knowledge of hypertension patients increased almost half (46%) were in the good category. Knowledge of hypertension patients increased after getting information through counseling activities about a low salt diet. Suggestions for clinics are expected to hold regular and periodic health education or promotion programs to provide information so as to increase the knowledge of hypertension patients